THE ROLE OF SOCIAL STUDIES TEACHERS IN SHAPING STUDENTS’ CHARACTER BASED ON THE PANCASILA STUDENT PROFILE (P5) AT SMPN 5 TAROGONG KIDUL, GARUT - Farhan; Eldi Mulyana; Sela Oktariza; Sudarmi (Journal Civics And Social Studies, 2025)
Educators hold a vital position in molding the personalities of learners by fostering an understanding of the Pancasila Student Profile (P5) principles within the educational environment. Instructors are not just providers of knowledge, but also serve as examples and guides in cultivating ethical principles, societal behaviors, and a feeling of national identity. Nevertheless, initial assessments at SMP Negeri 5 Tarogong Kidul indicate the presence of student actions that do not completely embody P5 ideals, such as limited self-reliance in learning, inconsistent engagement in dialogues, insufficient regard for differing viewpoints, and minimal attention to societal matters. This research endeavors to examine the function of social science instructors in developing student character that aligns with the Pancasila Student Profile at SMP Negeri 5 Tarogong Kidul, Garut. A qualitative research design with a descriptive technique is utilized for this study. Participants in the research comprise social science educators, students in the eighth grade, the Vice Principal for Academic Affairs, and the Vice Principal for Student Affairs, all chosen via purposive sampling. Information was gathered through observation, Interviews, and records, and subsequently examined utilizing the Miles and Huberman interactive framework. The findings revealed that social science educators functioned as enablers, representations, and strengtheners of character qualities through incorporating P5 values into social science instruction. The methods employed encompassed collaborative conversations, learning via projects, and the practice of P5 principles, even though difficulties remained in their execution. Consequently, cooperation among every individual within the educational setting is essential to encourage the ongoing enhancement of the Pancasila Student Profile characteristics. Keywords : Social Studies Teacher Role, Pancasila Student Profile (P5), Character Education